Non-communicable airway disease and air pollution in three African Countries: Benin, Cameroon and The Gambia - B. Awokola; H. Lawin; O. Johnson; A. Humphrey; D. Nzogo; L. Zubar; G. Okello; S. Semple; E. Awokola; G. Amusa; N. Mohammed; C. Jewell; et al. (IJTLD Open)
BACKGROUND: Air pollution exposure can increase the risk of development and exacerbation of chronic airway disease (CAD). We set out to assess CAD patients in Benin, Cameroon and The Gambia and to compare their measured exposures to air pollution. METHODOLOGY: We recruited patients with a diagnosis of CAD from four clinics in the three countries. We collected epidemiological, spirometric and home air pollution data. RESULTS: Of the 98 adults recruited, 56 were men; the mean age was 51.6 years (standard deviation ±17.5). Most (69%) patients resided in cities and ever smoking was highest in Cameroon (23.0%). Cough, wheeze and shortness of breath were reported across the countries. A diagnosis of asthma was present in 74.0%; 16.3% had chronic obstructive pulmonary disease and 4.1% had chronic bronchitis. Prevalence of airflow obstruction was respectively 77.1%, 54.0% and 64.0% in Benin, Cameroon, and Gambia. Across the sites, 18.0% reported >5 exacerbations. The median home particulate matter less than 2.5 μm in diameter (PM2.5) was respectively 13.0 μg/m3, 5.0 μg/m3 and 4.4 μg/m3. The median home carbon monoxide (CO) exposures were respectively 1.6 parts per million (ppm), 0.3 ppm and 0.4 ppm. Home PM2.5 differed significantly between the three countries (P < 0.001) while home CO did not. CONCLUSION: Based on these results, preventive programmes should focus on ensuring proper spirometric diagnosis, good disease control and reduction in air pollution exposure.